Zasada dobrowolności stosowania normy technicznej w polskim systemie prawa – geneza, historia, współczesność - Łukaszczyk, Mateusz (Studia Prawa Publicznego, 2026)
The legal nature of standards, particularly the Polish Standard, has undergone four fundamental changes in Poland’s recent history: from a voluntary, neutral system in the Second Polish Republic to a largely mandatory system in the People’s Republic of Poland, and from a partially voluntary system at the dawn of the Third Polish Republic to a fully voluntary system in the twenty-first century. A clear connection exists between the legal framework governing technical standards and the nature of the economic system in place at a given time: in a free-market economy, a voluntary model prevails, whereas in a centrally planned economy, a mandatory model existed. European and international standardization have had a decisive influence on the current model of Polish standardization. Today, standardization is governed by the principle of voluntary application of standards, which has been enshrined in law at the national, EU, and international levels. In line with this principle are indicative references to standards in regulations. A pertinent example of such references are the harmonized standards in EU legislation. The 2002 Standardization Act contains no delegation of authority to establish an obligation to apply standards, neither at the level of an act (statute) nor at the level of a minister’s regulation. Exclusive references to standards in regulations remain incompatible with the Polish legal system and the principle of voluntary compliance. Such references should be interpreted not as an obligation to apply a standard but as a recommendation to apply the standard referred to in the legal provision. Applying the referred standard is one of the ways to meet legal requirements, and the duty holder may apply another standard with an equivalent or higher level of safety. However, the concept of the obligation to apply the referred standards would require an amendment to the Standardisation Act of 2002, which would allow for such an exception. This amendment would also require adapting the standardization system to the principles related to constitutional sources of law.